Unemployment and transitions in the Turkish labor market: evidence from individual level data - H. Mehmet Taşçi; Aysit Tansel (Institute for the Study of Labor (IZA), 2005)
This paper provides a systematic analysis of the determinants of transitions in the Turkish labor market by using the Household Labor Force Survey (HLFS) panel data of 2000 and 2001. We provide two types of evidence. First, we compute annual transition probabilities between the labor market states of employment, unemployment and out-of-the labor force under Markovian assumptions by gender and rural-urban residence and marital status. Transition probabilities are used to analyze the differences in unemployment rates of these groups. Second, we present estimates of gender-specific multinomial logit models to analyze the determinants of men's and women's transition probabilities across labor market states. We find that urban women have higher unemployment rates than urban men because they have lower probability of exiting unemployment for a job and higher probability of exiting employment for unemployment. Non-married men and women's unemployment rates are higher than married men and women's. This may be attributed to the higher probability of non-married men and women's to lose a job. Increases in education level are found to decrease the probability of losing a job. University graduates of two-year and over are more likely to find employment compared to non-graduates. Younger individuals are more likely to lose a job but older individuals are less likely to find a job from unemployment. In provinces with high unemployment the probability of obtaining a job is lower from unemployment. The findings indicate negative duration dependence for women, but not for men. Men improve their chances of obtaining a job if they use newspapers or worker agents.
Keywords: J23; J64; J16; 330; panel data; unemployment; transition probabilities; gender; Turkey